Antibacterial compounds derived from marine Streptomyces aureofaciens A3 through in-silico molecular docking - Srikandace, Yoice; Syani, Ira Rhabbiyatun; Wahhaab, Aisha; Kamarisima, Kamarisima; Putri, Sastia Prama; Aditiawati, Pingkan (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Streptomyces aureofaciens widely produces the antibiotic tetracycline and many other compounds during fermentation. The compounds have yet to be known for their antibacterial potential. This work aims to determine new antibiotics or other possible antibacterial compounds produced by marine S.aureofaceiens A3 through an in silico molecular docking method. The ethyl acetate (EA) extracts from fermented marine S. aureofaciens A3 in ISP4 medium enriched with seawater components showed strong antibacterial activity.  The antibacterial activity of EA extracts during 6-12 days of fermentation was carried out by the Kirby-Bauer method and the compounds of EA extracts were analyzed by GC/MS. Compounds identified by GC/MS were ligands for an in silico molecular docking study against four target proteins (DNA gyrase, topoisomerase IV, PBP 1a, and DHFR) of pathogenic bacteria. The drug-likeness of selected chemicals as antibacterial agents was assessed using Lipinski's Rule of Five. The results showed the prospective compounds as a narrow-spectrum antibacterial, including 3,5-di-tert-Butyl-4-hydroxyphenylpropionic acid against PBP 1a and Benzenepropanoic acid, and 3,5-bis (1,1-dimethyl ethyl)-4-hydroxy-, methyl esters against DHFR. Substances with broad-spectrum antibacterial activity, such as 3-Acetylphenanthrene and 3-(p-Ethoxyphenyl)-5-(O-tolyloxymethyl)-2-oxazolidone, against multitarget DNA gyrase B and DHFR, 7,9-Di-tert-butyl-1-oxaspiro (4,5) Deca-6,9-diene-2,8-dione against PBP1a and DHFR, and isobenzofuro [5,6-b] benzofuran-8-carboxylic acid, 1,3-dihydro-7,10-dimethoxy-9-methyl-1-oxo-, methyl ester against DNA gyrase B, PBP 1a, and DHFR. On the 12th day of fermentation, two compounds were identified: isobenzofuro[5,6-b] benzofuran-8-carboxylic acid, 1,3-dihydro-7,10-dimethoxy-9-methyl-1-oxo-, methyl ester, and 3-(p-Ethoxyphenyl)-5-(O-tolyl oxy methyl)-2-oxazolidone.  This is the first report that these two compounds, known as potential drugs like antibiotics through in silico molecular docking, were first produced by Streptomyces species.